2011
DOI: 10.4236/gm.2011.13012
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Cut Slopes Using Continuous Slope Mass Rating and Kinematic Analysis in Rudraprayag District, Uttarakhand

Abstract: In mountain terrains of Himalaya, road and highway networks play a vital role in remote areas for transportation, public network and all kind of socio-economic activities. The stability of rock slopes along the roads and highways is a major concern in these hilly regions. Any kind of slope failure may lead to disruption in traffic, loss of properties and lives/injuries as well as environmental degradation. The unplanned excavations of rock slopes for construction or widening purposes may undermine the stabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 5 publications
(6 reference statements)
0
33
0
1
Order By: Relevance
“…In comparison to RMR basic , the detailed quantitative definition of the correction factors is one of the most important advantages of SMR classification (Tomas et al 2007(Tomas et al , 2012. Several researchers have also used continuous SMR (CSMR) approach, a modification of SMR by Romana (1985) for slope (Tomas et al 2007;Umrao et al 2011). SMR is a commonly used geo-mechanical classification for the characterization of rock slopes and can be numerically presented as follows:…”
Section: Slope Mass Ratingmentioning
confidence: 99%
“…In comparison to RMR basic , the detailed quantitative definition of the correction factors is one of the most important advantages of SMR classification (Tomas et al 2007(Tomas et al , 2012. Several researchers have also used continuous SMR (CSMR) approach, a modification of SMR by Romana (1985) for slope (Tomas et al 2007;Umrao et al 2011). SMR is a commonly used geo-mechanical classification for the characterization of rock slopes and can be numerically presented as follows:…”
Section: Slope Mass Ratingmentioning
confidence: 99%
“…The failure mechanisms usually instigate and follow preexisting discontinuities rather than breaking through intact rock. The stability problem of rock slopes along roads in the Himalaya is a major concern in most of the places [16]. It has been revealed that in hilly areas, especially in monsoon season, unplanned excavation of rock slopes for road construction and widening makes the slopes most vulnerable.…”
Section: Introductionmentioning
confidence: 99%
“…limit equilibrium method (LEM), finite element method (FEM), finite difference method (FDM) and distinct element method (DEM). The conventional techniques mainly include kinematic analysis and limit equilibrium techniques (Duncan & Wright, 1980;Kim et al 2002;Kumar & Sanoujam 2007;Umrao et al 2011). LEM is the conventional tool which is routinely used in analysis of loose slope soil/debris etc., whereas translational or rotational movements occur on distinct failure (Vishal et al 2010;Singh et al 2013b).…”
Section: Introductionmentioning
confidence: 99%